Differential expression and distribution of placental glutathione peroxidases 1, 3 and 4 in normal and preeclamptic pregnancy - Mistry, H.D.; Kurlak, L.O.; Williams, P.J.; Ramsay, M.M.; Symonds, M.E.; Broughton Pipkin, Fiona (Elsevier, 2010)
Preeclampsia is a pregnancy-specific condition affecting 2-7% of women and a leading cause of perinatal and maternal morbidity and mortality; it may also predispose the mother and fetus to increased risks of adult cardiovascular disease. The selenoprotein glutathione peroxidases (GPxs) have critical roles in regulating antioxidant status. Objectives, study design and main outcome measures: Immunohistochemical measurements of GPx 1, GPx3 and GPx4 protein expression were performed on samples taken from three standardised sampling sites between the cord insertion and the periphery of the placenta from 12 normotensive, and 12 preeclamptic women to establish if their expression differed between sampling sites. Total GPx activities were also examined from the three sampling sites of these placentae. Results: There were highly significant reductions in overall immunohistochemical staining of all 3 GPxs in the preeclampsia compared to normotensive placentae (GPx1: P = 0.016; GPx3: P = 0.003; GPx4: P < 0.001). Furthermore, graded differences in expression between the standardised placental sampling sites were also found for GPx3 (higher in the inner region, P = 0.05) and GPx4 (higher in the periphery, P = 0.02) but not GPx1. Placental GPx enzyme activity was also significantly reduced in tissue from preeclamptic women as compared to normotensive women (P = 0.007; the difference was more pronounced nearest the cord insertion). Conclusions: We have shown highly significant reductions in expression of all three major classes of GPx in placentae from women with preeclampsia, and distribution gradients in activity, which may relate to the differential oxygenation of regions of the placenta.